2016
DOI: 10.3329/bjnm.v17i2.28194
|View full text |Cite
|
Sign up to set email alerts
|

Dosimetric Comparison of Different 3DCRT Techniques in Left Breast Cancer Radiotherapy Planning

Abstract: Treatment plan of 10 patients with left-sided breast cancer treated to a prescribed dose of 50 Gy in 25 fractions were selected. The treatment plans were generated by using an Elekta Precise PLAN treatment plan system (TPS) in three different ways namely M1 method, M2 method and M3 method for evaluation of dosimetric parameters based on three dimensional conformal radiotherapy (3DCRT) technique. Pencil beam calculation algorithm was used for dose calculation of Planning Treatment Volume (PTV) as well as Organ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 7 publications
0
2
0
1
Order By: Relevance
“…Salah satu teknik penyinaran dalam radioterapi adalah threedimensional conformal radiation therapy (3D-CRT). Teknik ini masih banyak diaplikasikan pada beberapa kasus pengobatan kanker seperti kanker payudara [1,2] dan kanker prostat [3]. Pemilihan sudut penyinaran merupakan salah satu langkah yang sangat penting dalam perencanaan pengobatan.…”
Section: Latar Belakangunclassified
“…Salah satu teknik penyinaran dalam radioterapi adalah threedimensional conformal radiation therapy (3D-CRT). Teknik ini masih banyak diaplikasikan pada beberapa kasus pengobatan kanker seperti kanker payudara [1,2] dan kanker prostat [3]. Pemilihan sudut penyinaran merupakan salah satu langkah yang sangat penting dalam perencanaan pengobatan.…”
Section: Latar Belakangunclassified
“…Although breast treatment methods continuously improve with technological development, there is still not an accepted standard method [7]. Many studies reported that the peak incidence of radiation pneumonitis is within three months after completion of radiation treatment [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…5 Radiotherapy techniques include two-dimensional (2D) therapy, three-dimensional conformal radiotherapy (3DCRT), advanced conformal radiotherapy (intensity modulated radiotherapy, IMRT or volumetric modulated arc therapy, VMAT).But none of these are accepted as standard method for PMRT. 6 Despite the fact that 3DCRT has improved local control, normal tissue toxicities, particularly those of the underlying lung and heart, continue to be a concern. 7 IMRT and VMAT have been proved to be superior to 3DCRT in various sites like head and neck, central nervous system, lung, prostate etc.…”
Section: Introductionmentioning
confidence: 99%